Importance of chemical polymorphism in modern crop protection. Issue 7 (18th May 2022) - Olenik, Britta; Keil, Birgit; Jeschke, Peter
Abstract: The development of agrochemical products faces many scientific challenges. After selection of an agrochemical candidate its properties will have to be optimized to guarantee best bioavailability and stability under many different conditions in various formulation types. These challenges are influenced by the solid‐state properties of the active ingredient and this makes the selection of an optimized solid‐state form of modern agrochemicals at early development stages very valuable. The increasing awareness of the solid state of agrochemicals is reflected in the importance of polymorphism patent applications, which may enhance the risk of litigations. This review aims to present strategies for the solid‐form selection process of agrochemical development candidates. It introduces the different techniques for crystallization and analytics and demonstrates the influence of the solid state on different formulation types. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : The timely selection of the best optimized solid form at a very early stage of the development of modern agrochemicals has a significant impact on manufacurability, cost of goods and quality of marketed agrochemical products.